Trade, commerce, and the state in the Roman world - Bowman, Alan K.; Bowman, Alan K.; Wilson, Andrew; Wilson, Andrew (Oxford studies on the Roman economy, 2017)
In this volume, papers by leading Roman historians and archaeologists discuss trade within the Roman Empire and beyond its frontiers between c.100 BC and AD 350, and the role of the state in shaping the institutional framework for trade. Documentary, historical and archaeological evidence forms the basis of a novel interdisciplinary approach